Rapid, Standardized Method for Determination of Mycobacterium tuberculosis Drug Susceptibility by Use of Mycolic Acid Analysis - Parrish, Nicole (American Society for Microbiology (ASM), 2007)
Multidrug-resistant (MDR) Mycobacterium tuberculosis and extrensively drug-resistant (XDR) M. tuberculosis are emerging public health threats whose threats are compounded by the fact that current techniques for testing the susceptibility of M. tuberculosis require several days to weeks to complete. We investigated the use of high-performance liquid chromatography (HPLC)-based quantitation of mycolic acids as a means of rapidly determining drug resistance and susceptibility in M. tuberculosis. Standard susceptibility testing and determination of the MICs of drug-susceptible (n = 26) and drug-resistant M. tuberculosis strains, including MDR M. tuberculosis strains (n = 34), were performed by using the Bactec radiometric growth system as the reference method. The HPLC-based susceptibilities of the current first-line drugs, isoniazid (INH), rifampin (RIF), ethambutol (EMB), and pyrazinamide (PZA), were determined. The vials were incubated for 72 h, and aliquots were removed for HPLC analysis by using the Sherlock mycobacterial identification system. HPLC quantitation of total mycolic acid peaks (TMAPs) was performed with treated and untreated cultures. At 72 h, the levels of agreement of the HPLC method with the reference method were 99.5% for INH, EMB, and PZA and 98.7% for RIF. The inter- and intra-assay reproducibilities varied by drug, with an average precision of 13.4%. In summary, quantitation of TMAPs is a rapid, sensitive, and accurate method for antibiotic susceptibility testing of all first-line drugs currently used against M. tuberculosis and offers the potential of providing susceptibility testing results within hours, rather than days or weeks, for clinical M. tuberculosis isolates.